Art, science, and art therapy : repainting the picture - Kaplan, Frances (Jessica Kingsley Publishers, 2000)
Since its inception, art therapy has relied largely on theory "borrowed" from psychotherapeutic approaches. In this provocative and original book on art therapy, Frances Kaplan outlines a scientific approach to art therapy. Kaplan examines the relationship between art and science, delineating the role of research and encouraging a spirit of enquiry in art therapy. She looks at the latest scientific developments, especially those in biology, evolution, and brain science, and relates them to theories about the creation and interpretation of art. This leads her to show how art therapists would benefit from learning more about neurology and the physical effects of art on the brain, and from being able to apply this knowledge in their art therapy practice. The scientific evidence presented offers support for an art-based theory of art therapy. By demonstrating the relationship between two disciplines which are traditionally thought of as opposing, Kaplan challenges our assumptions about art therapy and issues a call for further research and debate.